Ocular manifestations of neurologic disease (St. Louis, Missouri, 1996)
The book offers a comprehensive on neuroopthalmplogy. In fact, the diagnosis of many neurologic entities can be made on the basis of eye signs or symptoms. A significant percentage of the nerve fibers in the central nervous system pass within the optic chiasm and are directly concerned with visual function. Moreover, the nerver fibers to the extraocular muscles comprise a significant part of the brain stem, and, like the visual fibers, travel through the brain in a lengthy, circuitous route. Thus, celebral vascular disease often will manifest as transient visual loss. An intracranial mass may produce disc edema or headache. Brain stem disease may cause acular motility or eyelid dysfunction. The book is written for the optometric clinician who desires a concise overview of the area. The topics are broad-based and cover those areas that are of major concern to the primary care optometrist
Keywords: eye manifestations,nervous systems,neuroophthalmology; diseases,diagnosis